Memaknai Penderitaan Yesus dalam Konsekuensi Pastoral - Yusuf Siswantara (Sekolah Tinggi Teologi Torsina Surakarta, 2020)
The article is a philosophical-theological reflection on an epidemic that is currently endemic throughout the world including in Indonesia, namely the Covid-19 Pandemic. This plague is considered a trigger for suffering everywhere and covers all aspects of human life. By using a qualitative literature approach and descriptive method, the article aims to present a pastoral reflection through the meaning of Jesus' suffering as a way of responding to pandemic events in a Christian context as a whole. In conclusion, reflection on the meaning of Jesus' suffering, including through the Easter celebration, provides positive energy in the life of Christian faith in responding to various difficult situations including the Covid-19 pandemic. AbstrakArtikel merupakan sebuah refleksi filosofis atas sebuah wabah yang se-dang mewabah di seluruh dunia termasuk di Indonesia, yakni Pandemi Covid-19. Wabah ini dianggap sebagai pemicu terjadinya penderitaan di mana-mana, dan mencakup seluruh aspek hidup manusia. Dengan meng-gunakan pendekatan kualitatif literatur dan metode deskriptif, artikel ber-tujuan menghadirkan sebuah refleksi pastoral melalui pemaknaan pende-ritaan Yesus sebagai cara merespon peristiwa pandemik dalam konteks orang Kristen secara menyeluruh. Kesimpulannya, refleksi atas pemakna-an penderitaan Yesus termasuk melalui perayaan Paskah memberikan energi positif dalam hidup beriman orang Kristen dalam merespon berba-gai situasi menyulitkan termasuk pandemi Covid-19.